2005
DOI: 10.1016/j.insmatheco.2004.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Copulas with fractal supports

Abstract: Using an iterated function system, the authors construct families of copulas whose supports are fractals. In particular, they show that the members of one family have supports with arbitrary Hausdorff dimensions in the interval (1,2). They also employ those copulas to construct more general bivariate distribution functions with fractal supports.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 8 publications
0
35
0
Order By: Relevance
“…Observe that the hypothesis that r and s are continuous functions is a necessary one, since otherwise counterexamples such as copulas with fractal support, as considered by Fredricks et al (2005), can be constructed. Let T = (t ij ) be a square matrix, with nonnegative entries whose sum equals 1, determining the following subdivision of the unit square …”
Section: A Limit Theoremmentioning
confidence: 99%
See 1 more Smart Citation
“…Observe that the hypothesis that r and s are continuous functions is a necessary one, since otherwise counterexamples such as copulas with fractal support, as considered by Fredricks et al (2005), can be constructed. Let T = (t ij ) be a square matrix, with nonnegative entries whose sum equals 1, determining the following subdivision of the unit square …”
Section: A Limit Theoremmentioning
confidence: 99%
“…Fredricks et al (2005) showed that for any copula C and any T = 1 there is a unique copula, C T , that depends only on T and satisfies T (C T ) = C T . Moreover, they showed that…”
Section: A Limit Theoremmentioning
confidence: 99%
“…Since the star product of copulas is a natural generalization of the multiplication of doubly stochastic matrices and doubly stochastic idempotent matrices are fully characterizable (see [10,25]) the following result underlines how much more complex the family of idempotent copulas is (also see [12] for the original result without idempotence).…”
Section: Remark 16 In Case the Copulas A B Are Absolutely Continuousmentioning
confidence: 99%
“…For general background on Iterated Function Systems with Probabilities (IFSP, for short), we refer to [16]. The IFSP construction of twodimensional copulas with fractal support goes back to [12] (also see [2]), for the generalization to the multivariate setting we refer to [30].…”
Section: The Ifs Construction Of (Very) Singular Copulasmentioning
confidence: 99%
See 1 more Smart Citation